Innate ability of goats to sense and avoid ingestion of noxious insects while feeding. Issue 2 (6th February 2019) - Berman, Tali S.; Messeri, Noa; Glasser, Tzach A.; Inbar, Moshe
Abstract : Large mammalian herbivores regularly encounter noxious insects on their food plants. Recent evidence revealed that goats efficiently avoid insect ingestion while feeding, yet it is unknown whether this ability is innate. We experimentally examined the behavioural responses of naive goat kids to a common insect, the spring-webworm ( Ocnogyna loewii ). We filmed and analysed the kids' behaviour while feeding and compared it to the behaviour described in adults. Naive kids sorted the webworms apart from the food without ingesting them (all webworms survived). They exhibited behaviours similar to those displayed by adults, demonstrating an innate ability to avoid insect ingestion. The kids detected webworms using tactile stimulation, obtained by repeatedly touching the leaves with their muzzles. This enabled them to pick webworm-free leaves (leaving 93% of webworms behind). While adults frequently shook or discarded leaves with webworms or spat out webworms, these behaviours were rare in kids. The kids' mean feeding rates doubled over the trials, indicating that their feeding efficiency on plants with and without insects improved with experience. As ingesting noxious insects could be fatal, innate avoidance is critical. These findings highlight the importance of direct interactions between mammalian and insect herbivores.